DAMPAK PANDEMI COVID-19 PADA KINERJA KEUANGAN BANK PERKREDITAN RAKYAT DI BALI - Srinadi, Anak Agung Ayu Dalem; Dwija Putri, I Gusti Ayu Made Asri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.06.TAHUN.2022DO - 10.24843/EEB.2022.v11.i06.p04, 2022)
The economic downturn due to the Covid-19 pandemic has an impact on the financial sector, one of which is Rural Banks (BPR). The results of previous studies showed inconsistent results and mostly carried out on commercial banks motivated to conduct research on the impact of the COVID-19 pandemic on the financial performance of rural banks. This study uses 132 BPRs in Bali as research samples with an observation period of 2019-2020. The variables used in this study are Capital Adequacy Ratio, BOPO Ratio, Return on Assets, Loan to Deposit Ratio, Non-performing Loan. The hypothesis was tested by means of two different tests of paired sample means. The results showed that the CAR, BOPO Ratio, ROA were between before and during the covid-19 pandemic. Meanwhile, the LDR and NPL did not show a significant difference between before and during the pandemic.